Effect of Finger and Hand Exercises among Amateur Pianist - S.F. Mariyam Farzana1 , Ashish Mathew A2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
BACKGROUND: Now days the number of students studying piano in tertiary institution is being increasing.The piano player is similar to athletic activity to play the notes accurately. Posture plays a vital role inpiano. Musicians are prone to injuries due to the nature of musical practice, inappropriate body postures andpotentially harmful playing techniques. Majority of amateur players are prone to injuries .Amateur pianoplayer experience pain in hands and fingers. The main objective of the study was to strengthen the fingerand hand muscles to reduce the level of pain. Methodology: Quasi Experimental study and convenientsampling.20 amateur piano players, were selected according to inclusion and exclusion criteria. Pre test wasdone to the participants using VAS score, hand grip dynamometer and cornell musculoskeletal discomfortquestionnaire. Finger and hand Exercise were given to the participants for 4 weeks . After 4 weeks of studyto analyze their level of pain, a hand held cornell musculoskeletal discomfort questionnaire, VAS scoreand hand grip dynamometer were used to find the effect of finger and hand exercise exercise. OutcomeMeasure: CORNELL MUSCULOSKELETAL DISCOMFORT QUESTIONNIARE, VAS SCORE,HANDGRIP DYNAMOMETER Result & Conclusion: The study concludes that there was significant reductionin the level of pain and also the hand grip was significantly improved